Disaster Mitigation Strategies to Enhance Community Preparedness for Earthquake Hazards in Liang Village, Salahutu District, Central Maluku - Wattimanela, Henry Junus; Elake, Alexander Yosep; Eka, Eka (Institut Teknologi Nasional, Bandung, 2025)
The initiative to promote earthquake disaster mitigation strategies in Liang Village is designed to enhance the community's awareness and readiness in the face of potential earthquakes. This effort is crucial due to Maluku's earthquake-prone geographical characteristics, underscoring the need to equip residents with essential knowledge and mitigation skills. The approach includes socialization, engaging discussions, and training in using basic technologies like the Avenza Maps and INATEW. Residents from various hamlets participated, with support from the Maluku Provincial BPBD. The outcomes reveal a notable improvement in participants' comprehension, as shown by the increase in pretest and posttest scores. Furthermore, the community's active involvement in establishing disaster preparedness groups reflects heightened collective awareness. The use of simple technology also enhances residents' capability to map their surroundings. This initiative has effectively become an educational, practical, and innovative model for community-based disaster risk reduction.